Późnośredniowieczna nadmorska osada rybacka w Pleśnej, gm. Będzino, pow. Koszalin - Janocha, Henryk (Wydawnictwo Naukowe UAM, 2005)
The article is aimed at presentation of different aspects related to discovery and analysis of materials from a late medieval seaside fishing village at Pleśna. It presents a scope of archaeological rescue excavations and assesses factors responsible for destruction of a cliff shore along with the settlement placed on top of it. Additionally, the article brings about analysis of excavated materials. The settlement chronology and development of the Pleśna region occupation is based upon archaeological evidence and historical sources.
Late medieval seaside fishing settlement at Pleśna, Będzino commune, Koszalin district